Descrição de cervejas tipo Pilsen por métodos sensoriais rápidos e análises físico-químicas - Victor Luiz Melo Dutra (2019)
Brazil is the third-largest beer producer in the world, after the United States and China. Besides this, in the last few years, beers produced by microbrewery have been growing in the Market. The goal of this study was to evaluate different sensorial methodologies in the description and characterization of Pilsen beers from two different market segments.The goal of this study was to characterize, evaluate and describe brands of Pilsen beers from two different market segment. The alcohol content, pH, titrated acidity, bitterness, color, real extract, apparent extract and extract in original wort. Besides, the samples were sensory evaluated by an acceptance test, Check-all-that-apply (CATA), Pivot Profile, and Projective Mapping. The samples produced by microbrewery differed from the market leader samples for pH, color and bitterness. Besides, all the samples showed an average higher than the hedonic term “indifferent”, which shows that they are close or inside the acceptance range. The results of the rapid descriptive tests showed differences when they are compared to the physicochemical results, but they were able to describe the samples in an effective way. Each test showed advantages and disadvantages. CATA is simple and faster being an option for studies with many evaluators. Pivot Profile is appropriate for exploratories studies. Finally, Projective Mapping is more suitable for comparative studies